Induction Of Labor Among Singleton Pregnancies In Six Palestinian Governmental Hospitals: A Population-Based Cohort Study - Hassan S; Laine K; Fosse E; Abu-Rmeileh NME; Ali-Masri HY; Zimmo M; Zimmo K; Vikanes Å; Ismail KM (Dove Medical Press, 2019)
Sahar Hassan,1 Katariina Laine,2,3 Erik Fosse,4,5 Niveen ME Abu-Rmeileh,6 Hadil Y Ali-Masri,4,5,7 Mohammed Zimmo,4,5,8 Kaled Zimmo,4,5,9 Åse Vikanes,4 Khaled M Ismail10,11 1Department of Nursing, Faculty of Pharmacy, Nursing and Health Professions, Birzeit University, Ramallah, Palestine; 2Department of Obstetrics, Oslo University Hospital, Ullevål, Oslo, Norway; 3Department of Health Management and Health Economics, Institute for Health and Society, University of Oslo, Oslo, Norway; 4Intervention Centre, Oslo University Hospital, Rikshospitalet, Oslo, Norway; 5Institute of Clinical Medicine, Faculty of Medicine, University of Oslo, Oslo, Norway; 6Institute of Community and Public Health, Birzeit University, Ramallah, Palestine; 7Department of Obstetrics, Palestine Medical Complex, Ramallah, Palestine; 8Department of Obstetrics, Al Shifa Hospital, Gaza, Palestine; 9Department of Obstetrics, Al Aqsa Martyrs Hospital, Gaza, Palestine; 10Department of Gynecology and Obstetrics, Faculty of Medicine in Pilsen, Charles University, Pilsen, Czech Republic; 11Biomedical Center, Faculty of Medicine in Pilsen, Charles University, Pilsen, Czech RepublicCorrespondence: Sahar HassanDepartment of Nursing, Faculty of Pharmacy, Nursing and Health Professions, Birzeit University, PO Box 14, Ramallah 627, PalestineTel +972599830158Email sjamal@birzeit.eduObjective: To explore rates and review practices regarding induction of labor (IOL) among singleton pregnancies in Palestine.Design: A prospective population-based cohort study.Setting: Six secondary and tertiary governmental hospitals located in the two regions of Palestine: West Bank and Gaza.Participants: Singleton pregnancies who had IOL in participating units during the study period were included (n=8290). Women having multiple gestations (1004), planned cesarean births (703), those admitted with cervical dilation >6cm (11228), and pregnancies with no record of cervical dilation and/or gestational age on admission (219) were excluded.Primary outcome measure: Rates of IOL in participating units and regions.Results: There were a total of 33,402 singleton births during the study period with an IOL rate of 24.8%. Rates of IOL significantly varied between units, ranging from 12.9% to 45.6% (P-value <0.05). The majority of women with no previous uterine scar were induced at gestational ages ≤40 weeks where 43.8% were induced at 39–40 gestational weeks (29.9% multiparous; 13.9% nulliparous) and 17.7% were induced between 37 and 38 gestational weeks (11.9% multiparous; 5.8% nulliparous).Conclusion: Significant variations in IOL practices between Palestinian hospitals and regions suggest overuse of IOL among singleton pregnancies in some units with the majority of these being performed before 40 weeks’ gestation. These findings indicate a gap between implementation of best evidence and current clinical practice.Keywords: childbirth, cohort study, induction of labor, Palestine, singleton, variations